Os povos indígenas na mira do capital: a devastação dos indígenas da América Latina pela superexploração do trabalho, pela expropriação e pelas crises climática e civilizacional - Daniel de Faria Galvão (2024)
The doctoral thesis, which will be presented here, aims to investigate the process of devastation of the indigenous people of Latin America by the capitalist mode of production. As a hypothesis, what is believed is that, from colonization until today, the devastation of the indigenous people of Latin America by imperialist nations has been sustained. The overexploitation of labor, expropriation and the climate and civilizational crises appear as the main drivers of this devastating process. In addition to denouncing this scenario of continuous violence, faced by the indigenous people of Latin America, the thesis that will be presented will also have a propositional function. Inspired by ecosocialism, what will be proposed is that the devastation of the indigenous people of Latin America be faced by a combination of struggles. The struggles of indigenous people for territory must be added to the struggles for the reduction of working hours, led by the proletariat 3 helping to combat a system of exploration, production and consumption that has decimated peripheral indigenous peoples and which, if not dismantled, could provoke the end of all humanity.